PREVALENCE OF URINARY INCONTINENCE IN WOMEN WHO PRACTICE CROSSFIT: AN INTEGRATIVE REVIEW (CIPEEX, 2026)
Introduction: Urinary incontinence (UI) is characterized by involuntary urine loss and affects between 10% and 40% of the global population, negatively impacting quality of life. Among the modifiable factors, physical activity can positively and negatively influence the occurrence of UI. CrossFit, a modality that involves high-intensity exercise, influences the pelvic floor muscles and increases the risk of UI. Objective: The objective of this study is to conduct an integrative review of the prevalence of urinary incontinence in women who practice CrossFit, highlighting associated factors and their impact on quality of life. Methodology: This integrative literature review, consulting MEDLINE, SciELO, Google Scholar, and Lilacs databases, was conducted between August and September 2025, considering articles published between 2020 and 2025, in Portuguese and English, focusing on women who practice CrossFit, aged 18 to 59. Results: Of the 13 articles, analysis revealed a prevalence of UI between 20% and 88.2% in CrossFit participants. Although often mild, the condition compromises exercise adherence and women's well-being. Factors such as training intensity and volume influence the occurrence of UI. Conclusion: Urinary incontinence is highly prevalent in female CrossFit participants, associated with young age and intense training load. It varies in frequency but impacts exercise adherence, quality of life, and repercussions.